A Study On Advertising Strategy In Selected Brands Of Washing Machines With Special Reference To Vasanth & Co In Thanjavur Branch - SRIDHAR, P.; SELVENDRAN, Dr. A. (The journal of contemporary issues in business and government, 2021)
Advertising provides opportunities for dramatizing the company and its products through the armful use of print sound and color sometimes; however the tools very success at expressiveness may dilute or distract from the message. Advertising cannot be as a company sales representative, the audience does not feel obligated to pay attention or respond. Advertising is able to carry on only a monologue, not a dialogue, with the audience. Message is normally addressed to a specific person and does not reach others. The message can be customized to appeal to the addressed individual. The message can be prepared berry quickly for delivery to an indexer to an individual. The appeal of public relations is based on its three distinctive qualities. News stories and features seem more authentic and credible to readers that ads do. Off guard: public relations can reach many prospects who might avoid salespeople and advertisements. The researcher has collected from the 62 days in sales of Vasanth & Co while claimed that an attractive widow display strategy has conducted for the improvement of sales for the 62 day from 1st Dec 2020 to 31 Jan 2021. In the connection the researcher has attempt to made a study on advertising strategy in selected brands in washing machines in Vasanth & Co In Thanjavur Town Branch. That the available sample data provides significant evidence to conclude a 5% level of significance that the window displays technique had increased the sales significantly after 31 days as well as profits. Overall profit position and sales position has increased from 97 units (brands) to 134 units after have made window display technique from 1st Dec 2020 to 31st Jan 2021 (60 days).